Pengukuran Kinerja Efektif Departemen Pengembangan Sistem Informasi dengan Metode Balanced Scorecard pada PT. Xyz - Suryani, Eli; Fadli, Muhammad (Bina Nusantara University, 2013)
Department of Information System Development at PT XYZ becomes a trigger in the movement of the Information Technology Development of the company. However it is not merely the fastest, the biggest or the most completed project that determine the success, but the most important is to align with the business strategy due to achieve the company’s goal and objective. Recognizing the performance does not only need a measurement system but also right measurements. The purpose of the study is to design an effective Key Performance Indicator in Departement of Information System Development that is aligned with current indicators to measure the success of company’s strategy execution. The choosen indicators are cascaded from company’s strategy map and information technology strategy map. The design uses balanced scorecard method according to data and information collected from executive interview, focus group discussion and workshop with the key persons in IT organization. Balanced scorecard method provides the integration of financial and non-fianncial factor for measurements. It allows different level formulation with same performance indicator flexibly. Recently, Department of Information System Development can monitor and develop its performance directionally.